Peran Akreditasi dalam Meningkatkan Mutu Pendidikan : Studi Kasus di MTs Al-Idris - Yeni Yulianti; Siti Qomariyah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Accreditation is a systematic evaluation process aimed at assessing the feasibility and quality of educational institutions, playing a significant role in driving improvements in education quality. This study aims to examine the role of accreditation in enhancing the quality of education at MTs Al-Idris, a madrasa committed to shaping an excellent generation based on Islamic values. Using a qualitative descriptive approach, this study found that accreditation serves not only as an indicator of quality achievements but also as a strategic tool driving holistic improvements, including in curriculum, teaching staff, facilities, and stakeholder satisfaction. These findings are expected to serve as a reference for madrasa in optimizing accreditation outcomes to achieve higher-quality education.